A single early warning signs (SEWS) system for recognizing clinically deterioration outperforms the national early warning score (NEWS) by having a lower activation threshold, broader clinical scope, and faster response time - Raúl J. Gazmuri; Rebecca Bieber; Calis Lim; Mylene Apigo; Ma Lea Martin (Resuscitation Plus)
Background: The National Early Warning Score (NEWS) is a vital-signs point summation system developed to identify patients at risk of adverse events including cardiac arrests, unplanned ICU admissions, and deaths. The points are usually calculated by the Electronic Health Record after charting, recommending local actions and Rapid Response System (RRS) activation when reaching ≥ 7 points. NEWS, however, lacks consistent evidence that it improves outcome and may lead to alarm fatigue. At our institution we operate a Single Early Warning Signs (SEWS) system for RRS activation with a broader range of abnormal signs, without point summation, and bedside assessment within 10 min. Methods: We analyzed 182 RRS activations using SEWS from July 1, 2022, to August 21, 2023, and compared the activation thresholds and dispositions that would have occurred had NEWS been used. Findings: At the time of RRS activation using SEWS, only 10 patients (5.5%) had scored ≥ 7 NEWS points. Of the remaining 172 patients, 158 (86.8%) scored 0 to 4 NEWS points considered low risk and 14 (7.7%) scored 5 to 6 NEWS points considered medium risk (p < 0.001). Yet, 122 patients (67%) were transferred to a higher level of care including 58 patients (31.8%) to ICU. The median in-hospital cardiac arrest during the reported period was 0.8 per 1000 hospital admissions, which is substantially lower than reported rates. Conclusion: SEWS operating with a broader clinical scope, lower activation threshold, and faster RRS activation outperformed NEWS markedly reducing in-hospital cardiac arrests.